2022
DOI: 10.31272/jeasd.25.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Steel Fiber Self-Compacting Concrete Hollow Deep Beams Under Torque

Abstract: The purpose of this paper was concerned of the behavior of six samples of deep beams under the influence of pure torsion. Such samples were self-compacting concrete (SCC) and two ratios of Steel Fibers (SF (were also added (0.75 % and 1.5 %). This study examined the behavior of the samples when pure torsion was applied and reacted to angles of torsion, longitudinal strains and concrete strains. It was obvious from the results of the test that the addition of steel fiber to the SCC mixture increased the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Recently, there have been efforts to study the behavior of concrete beams with longitudinal openings as follows Murtada and Yahyia [17] investigated the structural behavior of shallow self-compacting beams when the diameter of the holes was changed, and it was found that the ultimate load decreases with the increase in the diameter of the holes. Muhanad and Saad [18] Hadi et al [19] They found that circular holes are better than rectangular when used in deep beams to make longitudinal holes. Haider and Mortada [20] find that parabola shapes are better than round when used in the longitudinal holes of the T-beams.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been efforts to study the behavior of concrete beams with longitudinal openings as follows Murtada and Yahyia [17] investigated the structural behavior of shallow self-compacting beams when the diameter of the holes was changed, and it was found that the ultimate load decreases with the increase in the diameter of the holes. Muhanad and Saad [18] Hadi et al [19] They found that circular holes are better than rectangular when used in deep beams to make longitudinal holes. Haider and Mortada [20] find that parabola shapes are better than round when used in the longitudinal holes of the T-beams.…”
Section: Introductionmentioning
confidence: 99%